COMPARATIVE EFFECT OF ORGANIC AND INORGANIC FERTILIZER ON GROWTH AND YIELD OF TOMATO GENOTYPES, LYCOPERSICON ESCULENTUM (MILL.) - Adewusi, O. F. (FUDMA Journal of Sciences, 2024)
This research was carried out to determine and to compare the effect of moringa leaf extract, poultry manure and NPK fertilizer on the growth rate and yield of the tomato genotypes. The 10 tomato genotypes utilized for this study were obtained from the tomato germplasm collection at the National Center for Genetic Resources and Biotechnology (NACGRAB), Department of Plant Genetic Resources, Ibadan, Oyo state, Nigeria. The experiment was a potted and factorial experiment whereby the tomato genotypes were subjected to 4 treatments which comprises Treatment 1 (no fertilizer), Treatment 2 (moringa leaf extract), Treatment 3 (poultry manure), Treatment 4 (NPK fertilizer). The experiment was carried out at the Teaching and Research Farm, Federal University of Technology, Akure. Data were collected on 13 agronomic characters. The application of NPK 15:15:15 fertilizer was found to greatly influence the rate of growth and yield of the tomato genotypes followed by Poultry manure and Moringa leaf extract for all the characters studied. Genotypes NGB00724, NGB00711 and NGB00695 were found outstanding among the tomato genotypes in terms of number of fruits, number of clusters, individual fruit weight and yield per plant irrespective of the type of fertilizer applied.Hence, these tomato genotypes could be improved upon and released as high yielding tomato varieties to farmers. The use of moringa leaf extract and poultry manure to produce tomato is a worthwhile alternative in place of NPK fertilizer.